ANALISIS KEMITRAAN DESA TLOGOJATI-PT TAMBI: PEMBERDAYAAN MASYARAKAT MELALUI OPTIMALISASI LAHAN DAN TENAGA KERJA LOKAL - Muhammad Saeful Bahri (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2025)
Community empowerment emphasizes the effective mobilization of local resources and active participation to stimulate local economic development. This study seeks to examine the partnership between the Tlogojati Village Government and PT Tambi in the management of village-owned land assets, applying the Asset-Based Community Development (ABCD) framework and Public–Private Partnership theory to expand employment opportunities for local residents. Optimizing village assets is a critical aspect of rural development, as it contributes to improving community welfare. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings indicate that the partnership was established on a mutually beneficial basis: the village government contributed village land as a productive asset, while PT Tambi provided managerial expertise in tea plantation operations. This collaboration generated tangible outcomes, including increased employment in production, maintenance, and processing activities, as well as growth in Village Original Revenue (PADes). Nevertheless, the study identified several challenges, particularly limited land value and the need for greater transparency in asset management. Overall, the partnership represents a best practice in asset-based community empowerment, although strengthening institutional capacity and expanding partner diversification remain essential to ensure long-term sustainability.